2022
DOI: 10.1038/s41598-022-25926-4
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of thickened carbonated cola in older patients with dysphagia

Abstract: Carbonated beverages initiate the swallowing reflex earlier than water and have a shorter pharyngeal transit time. However, the effects of carbonation in thickened beverages of the same flavor on swallowing dynamics have not been reported. Therefore, we investigated the effects of thickened carbonated beverages on swallowing in patients with dysphagia by comparing the swallowing dynamics between thickened carbonated and thickened non-carbonated beverages. We enrolled 38 patients with dysphagia and divided them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Furthermore, carbonated water is less likely to be aspirated or left in the pharynx than non-carbonated liquids in patients with central nervous system disease (51,52). We and other laboratories have reported that thickened carbonic acid further improves swallowing function (53,54).…”
Section: Swallowing Function-carbonation and Tastementioning
confidence: 98%
“…Furthermore, carbonated water is less likely to be aspirated or left in the pharynx than non-carbonated liquids in patients with central nervous system disease (51,52). We and other laboratories have reported that thickened carbonic acid further improves swallowing function (53,54).…”
Section: Swallowing Function-carbonation and Tastementioning
confidence: 98%
“…to decrease both the penetration and aspiration compared with noncarbonated thin liquids (NCTL) in the examination of oropharyngeal swallowing in 17 adults with pharyngeal delay 337) , the effects of carbonation in thickened beverages of the same flavor on swallowing dynamics have not been reported. This was studied for 38 dysphagia patients 338) . The residue in vallecula and pyriform sinus were found reduced by CTL cola than by NCTL cola.…”
Section: Effects Of Chemical Sensesmentioning
confidence: 99%
“…The onset of the swallowing reflex was significantly earlier in the group of CTL than in the group of NTCL. Saiki et al 338) concluded that CTL cola was more beneficial for dysphagia patients than NTCL. Similar conclusions were reported [339][340][341] .…”
Section: Effects Of Chemical Sensesmentioning
confidence: 99%